Instrumental analysis of ferrous sulfate-containing preparations - Andag, Aurea A.; Concepcion. Adoracion B.; Cruz, Ileana R.; Fernando, Elena S.; Santos, Rizalina B. (Manila College of Pharmacy, University of the Philippines, 1988)
Two methods for the assay of ferrous ion in ferrous sulfate-containing tablets and capsules are described. The first method is based on the spectrophotometric measurement of the chromophore produced by reacting the ferrous ion with alpha, alpha'-dipyridyl (or 2, 2'-bipyridine). For comparison purposes, the absorbance of the said reaction was also measured via the electrophotomer/colorimeter. The second method used o-phenanthroline as the colorimetric reagent. The absorbance was measured using the same instruments.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1988.
Keywords: Ferrous sulphate; Instrumental analysis